Research Experiences of STEM Learners in Science Investigatory Projects and the Level of Support Curriculum Integration - Camara, Jun S. (International Journal of STEM Education for Sustainability, 2025)
This study aimed to assess the curricular experiences of STEM learners in writing their science investigatory projects as a requirement under the Special Science Class, which served as their basis for supporting the integration of the relevant skill sets in the research curriculum. To do this, the researcher developed and validated a survey questionnaire which was administered in February 2024 during a training workshop, and the data were processed using SPSS. The findings showed that most of the respondents (n=54) had had an experience concerning the 11 skill sets in writing, with three skill sets emerging as experienced by all of them. Further, when asked how they think these skill sets could be formally integrated into a research subject for the Special Science Class, the findings showed Very High support for integrating them. Policy recommendations for STEM education for a sustainable curriculum are provided.